Community pharmacists' knowledge and perceptions on risk management plans in the Southern Region of Portugal. (1st October 2016) - Duarte, Maria; Ferreira, Paula; Soares, Maria; Martins, Ana Paula; Cavaco, Afonso
Abstract: A Risk Management Plan (RMP) is a detailed description of the activities and interventions designed to identify, characterize, prevent, or minimize risks relating to medicine's use. The objective of this article is to assess RMP-related knowledge of community pharmacists and explore the reasons behind any potential issues with its use. This study has two focus points: (1) A cross-sectional survey within a sample of pharmacies in the area covered by the South Pharmacovigilance Center; and (2) a focus group (FG) with key-informants, in order to increase the explanatory scope of quantitative results. In total, 41.6% of the participants in the study knew what a risk management plan was, but 50% rated their knowledge as poor. According to focus group participants, this lack of knowledge seems to be related to three main factors: (i) this subject not being addressed during graduation training; (ii) professionals' attitude; and (iii) lack of communication among different stakeholders. It is recommended that there is enhanced academic training in risk management. There is an important call for attitudinal change interventions and further investigation in monitoring RMP use and impact. A closer articulation between the regulator, the pharmaceutical society, associations, and industry is needed to promote and boost this topic among community pharmacists.